Monitoring dan Evaluasi Pelatihan Pembinaan Kesadaran Bela Negara Lingkup Pekerjaan bagi Aparatur Sipil Negara Kementerian Lingkungan Hidup - Inge Salsabila Suryaman; Fitri Rosvianti; Sagita Ludyna Sanosie (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
The National State Defence Development Training (PKBN) plays a strategic role in shaping the National Defence character of employees in the workplace. Monitoring and evaluation is a systematic process that identifies the effectiveness and strengths of the PKBN program that has been implemented. The government, in its efforts to realize an advanced, prosperous, sovereign, and globally competitive Unitary State of the Republic of Indonesia, is committed to the vision of "Golden Indonesia 2045" as the nation’s grand ideal. One crucial aspect of realizing this vision is the need for quality Human Resources (HR) who possess a strong national defence character, as outlined in Presidential Decree No. 115/2022 regarding the 2020-2044 PKBN Master Plan. This effort aims to develop professional HR who not only excel in their respective fields but also have a deep sense of patriotism and awareness of the importance of defending the nation from various threats that may jeopardize its sovereignty, territorial integrity, and national security. The implementation of PKBN for the Ministry of Environment and Forestry (KLHK) is highly relevant to its mandate and strategic role in preserving the environment and ensuring the sustainability of Indonesia’s natural resources. This establishes a distinct urgency, as KLHK is considered the frontline institution in environmental management. Its personnel face multidimensional challenges that are not only technical and ecological in nature but also ideological and national in scope. Threats to national sovereignty today no longer come solely from military aspects, but also from environmental degradation, unsustainable exploitation of natural resources, and the impacts of global climate change, all of which can weaken national resilience. The method in this research is a qualitative method with a data analysis process of the implementation of the National Defense Awareness Development Training (PKBN) held at the National Defense Training Center of the Ministry of Defense's Human Resources Development Agency (BPSDM). Data collection techniques include in-depth interviews, participatory observation, and document analysis of the Evaluation of the Implementation of the PKBN Training Scope of Work for ASN of the Ministry of Environment in 2025 at the National Defense Training Center of the Ministry of Defense's Human Resources Development Agency (BPSDM).The findings of this study conclude that PKBN education is not merely an institutional necessity but a long-term strategic investment in Indonesia’s stability, sovereignty, and national resilience. Therefore, continuous improvement of the PKBN program with an adaptive and relevant approach to evolving global challenges is essential to cultivate a society that is productive, responsible, and nationally conscious. hreats that may jeopardize its sovereignty, territorial integrity, and national security. The implementation of PKBN for the Ministry of Environment and Forestry (KLHK) is highly relevant to its mandate and strategic role in preserving the environment and ensuring the sustainability of Indonesia’s natural resources. This establishes a distinct urgency, as KLHK is considered the frontline institution in environmental management. Its personnel face multidimensional challenges that are not only technical and ecological in nature but also ideological and national in scope. Threats to national sovereignty today no longer come solely from military aspects, but also from environmental degradation, unsustainable exploitation of natural resources, and the impacts of global climate change, all of which can weaken national resilience. The method in this research is a qualitative method with a data analysis process of the implementation of the National Defense Awareness Development Training (PKBN) held at the National Defense Training Center of the Ministry of Defense's Human Resources Development Agency (BPSDM). Data collection techniques include in-depth interviews, participatory observation, and document analysis of the Evaluation of the Implementation of the PKBN Training Scope of Work for ASN of the Ministry of Environment in 2025 at the National Defense Training Center of the Ministry of Defense's Human Resources Development Agency (BPSDM).The findings of this study conclude that PKBN education is not merely an institutional necessity but a long-term strategic investment in Indonesia’s stability, sovereignty, and national resilience. Therefore, continuous improvement of the PKBN program with an adaptive and relevant approach to evolving global challenges is essential to cultivate a society that is productive, responsible, and nationally conscious.